Behavioral Economics and Macroeconomic Models - John C. Driscoll; Steinar Holden (Center for Economic Studies and ifo Institute (CESifo), 2014)
Over the past 20 years, macroeconomists have incorporated more and more results from behavioral economics into their models. We argue that doing so has helped fixed deficiencies with standard approaches to modeling the economy—for example, the counterfactual absence of inertia in the standard New Keynesian model of economic fluctuations. We survey efforts to use behavioral economics to improve some of the underpinnings of the New Keynesian model—specifically, consumption, the formation of expectations and determination of wages and employment that underlie aggregate supply, and the possibility of multiple equilibria and asset price bubbles. We also discuss more broadly the advantages and disadvantages of using behavioral economics features in macroeconomic models.
Keywords: E20; E30; D80; 330; behavioral macroeconomics; New Keynesian model